Strategi Manajemen Mengoptimalkan Kinerja dengan Konsep Beyond Budgeting - Badar Murifal (Universitas Batanghari Jambi, 2021)
There are two important elements that create an environment of high freedom for managers and employees, namely the company management culture and the availability of a clear information system as the basis for the management process. The new model of leadership is based on the principle of empowering managers and employees, as well as an adaptable management process. This new leadership principle must be able to unlock all potential managers and employees in running the organization so that they can react appropriately and quickly when facing new opportunities and market risks. To be successful, members of the beyond budgeting project must include control specialists, human resource management, change management, and computer experts. Not all companies are able to provide all the required resources. In traditional budgeting systems, targets are set based on financial figures and are negotiated centrally. In beyond budgeting, targets are based on high key performance indicators, such as the ratio of return on capital, free cash flows or cost to income. Performance appraisals are no longer carried out for the long term (annually), but are carried out in a shorter period of time on a regular basis and are rolling and decentralized. Beyond Budgeting is the idea of abolishing traditional budgeting processes to eventually improve management control over an organization. By abandoning traditional budgeting processes, a company aims to establish a highly decentralized organizational system and adaptive set of management processes.